Changes in Occupational Tasks and Their Association with Individual Wages and Occupational Mobility - Alexandra Fedorets (German Economic Review, 2019)
This study provides novel evidence on the relevance of task content changes between and within occupations to wage dynamics of occupational changers and stayers. I use individual-level, cross-sectional data featuring tasks performed on the job to compute a measure of proximity of job contents. Then, I merge this measure to a large-scale panel survey to show that occupational changers experience a wage growth that is declining when the accompanying alterations in task contents are big. For occupational stayers, alterations in task contents generate a positive wage component, beyond tenure effect. However, the results are not robust with respect to the choice of proximity measure and over time.
Keywords: J24; J62; 330; Human capital; wage premium; occupational change; task-based approach